Phytogenics From Sage and Lemon Verbena Promote Growth, Systemic Immunity and Disease Resistance in Atlantic Salmon (Salmo salar) - Salomón, Ricardo; Furones, M. Dolors; Reyes-López, Felipe E.; Tort, Lluis; Firmino, Joana P.; Quintela, José C.; Pinilla-Rosas, José M.; Vallejos-Vidal, Eva; Gisbert, Enric (Frontiers in Marine Science, 2022)
The transcriptomic response of the head kidney, the main lymphohematopoietic tissue of the body, was evaluated in Atlantic salmon (Salmo salar) smolts fed a functional feed containing a phytogenic rich in verbascoside and triterpenic compounds like ursolic acid. Fish (initial body weight = 55.0 ± 0.1 g) were fed two experimental diets (40% crude protein, 22% crude fat; 21.6 MJ/kg gross energy) that only differed in the phytogenic content (0.1% inclusion). Each diet has six replicates and was tested over a period of 133 days. The tested zootechnical feed additive a medicinal plant leaf extract (MPLE) obtained from sage (Salvia officinalis) and lemon verbena (Lippia citriodora). At the end of the trial, smolts fed the MPLE diet were heavier than their congeners from the control group (271.5 ± 7.9 g vs. 240.2 ± 19.3 g, respectively; P < 0.05). Feed conversion ratio (FCR) values in fish fed the control diet were higher than those in fish fed the MPLE diet (FCRcontrol diet = 1.27 ± 0.08 vs. FCR0.1% MPLE diet = 1.08 ± 0.05; P < 0.05). The immunomodulatory properties of the functional diet were evaluated by means of an in vivo challenge with Aeromonas salmonicida subsp. salmonicida (1 × 107 CFU mL–1). The microarray analysis of head kidney samples from both dietary groups revealed 1,178 differentially expressed genes (802 upregulated and 376 downregulated). Among them, several biological processes related to immunity were identified in fish fed the MPLE diet (i.e., interferon-gamma-mediated signaling pathway, antigen processing and presentation of peptide antigen via MHC class II, autophagy, regulation of i-kappaB kinase/NF-kappaB signaling, and leukocyte activation). Results from the bacterial challenge showed that survival rates were higher in smolts from the MPLE group (90.6 ± 6.4%) in comparison to the control group (60.7 ± 13.5%), confirming the functional benefits of the phytogenic in terms of host’s immunity and disease resistance. Biological processes such as cytoskeleton organization and regulation of cellular protein metabolic process detected in fish fed the MPLE diet supported the metabolic changes related to increased somatic growth promoted. The present findings showed that the inclusion at 0.1% of the tested MPLE obtained from sage and lemon verbena in diets for Atlantic salmon smolts promoted somatic growth, and enhanced their systemic immune response and reduced mortality when fish were challenged with A. salmonicida cumulative, the causative agent of furunculosis in salmonids.